2015
DOI: 10.2500/ajra.2015.29.4216
|View full text |Cite
|
Sign up to set email alerts
|

Immunomodulatory Effect of Tonsil-Derived Mesenchymal Stem Cells in a Mouse Model of Allergic Rhinitis

Abstract: Administration of T-MSC effectively reduced allergic symptoms and inflammatory parameters in the mouse model of AR. T-MSC treatment reduced Th2 cytokines and OVA-specific IgE secretion from B cells. In addition, innate cytokine (IL-25 and IL-33) expression and eotaxin messenger RNA expression was inhibited in the nasal mucosa, which is suggestive of the mechanism of reduced allergic inflammation. Therefore, T-MSC treatment is potentially an alternative therapeutic modality in AR.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
23
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 31 publications
(24 citation statements)
references
References 25 publications
1
23
0
Order By: Relevance
“…Moreover, studies for T-MSCs described an immunomodulatory effect on degenerative or inflammatory diseases [17][18][19][20]. Our previous study also demonstrated an immunomodulatory effect of T-MSCs in a mouse model of allergic rhinitis [21]. However, conditioned media released by T-MSCs (T-MSCs-CM) are more feasible for preparation and application than T-MSCs themselves.…”
Section: Introductionmentioning
confidence: 89%
See 1 more Smart Citation
“…Moreover, studies for T-MSCs described an immunomodulatory effect on degenerative or inflammatory diseases [17][18][19][20]. Our previous study also demonstrated an immunomodulatory effect of T-MSCs in a mouse model of allergic rhinitis [21]. However, conditioned media released by T-MSCs (T-MSCs-CM) are more feasible for preparation and application than T-MSCs themselves.…”
Section: Introductionmentioning
confidence: 89%
“…Therefore, in this study, we investigated the immunomodulatory effect of T-MSCs-CM on the allergic rhinitis mouse model and also evaluated the inhibitory mechanism of T cell activation by T-MSCs-CM. [21], we harvested tonsil tissue after tonsillectomy and it was cultured in stem cell-enrichment condition, which consisted of RPMI-1640 media (Gibco, Grand Island, NY) with 10% fetal bovine serum (Gibco) and 1% penicillin and streptomycin (Gibco) at a density of 2 × 10 4 cells/cm 2 . The following day, the cells were switched to serum-free RPMI-1640 media.…”
Section: Introductionmentioning
confidence: 99%
“…In addition to those distinct characteristics, TMSC exhibit immune regulatory activity like other MSC. Previously, TMSC have been shown to have an immunomodulatory effect on allergic rhinitis in mice via both the reduction of Th2 cytokines and ovalbumin-specific immunoglobulin E secretion from B cells [ 26 ]. In this report, the authors suggested the inhibition of innate cytokines IL-25 and IL-33 as the underlying mechanism.…”
Section: Introductionmentioning
confidence: 99%
“…Eotaxin-2 expression was evident in all analysed subgroups with a significant upregulation in adenoids, suggesting an involvement of Th2- immune responses as eotaxin-2 which is known to play a crucial role in the pathogenesis of atopic diseases involving Th 2- cell activation 41 . Significant upregulation of eotaxin-2 has been observed in bronchial asthma 42 and allergic rhinitis 43 . However, the significance of eotaxin-2 expression in lymphatic tissue of the Waldeyer’s tonsillar ring still largely remains uncertain, like their role in the maturation of the adaptive immune system in the mucosa of the upper aerodigestive tract.…”
Section: Discussionmentioning
confidence: 99%